Implementation of Policies for the Development of Neglected Children - Nurmalia, Indah; Sari, Siti Nadia; Khumayah, Siti; Rahmayanti, Rahmayanti (Indonesian Journal of Advanced Research, 2025)
This study examines the implementation of the Neglected Children Development Program Policy by the Cirebon Regency Social Services Agency. The objective is to analyze the development program, identify obstacles, and evaluate the policy's impact. The method used is descriptive qualitative through interviews, observation, and documentation, as well as data validation through source triangulation. Referring to Charles O. Jones's policy implementation theory, the results show that the organizational indicators function well despite being constrained by a lack of staff, facilities, and coverage. Interpretation indicators indicate that the program meets children's needs, but is constrained by facilities and budget. Application indicators show progress thanks to inter-agency collaboration. This study recommends improving human resources, facilities, budgets, and synergy between related institutions.